Middleware 2010 ACM/IFIP/USENIX 11th International Middleware Conference, Bangalore, India, November 29 - December 3, 2010. Proceedings - Gupta, Indranil; Mascolo, Cecilia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 11th International Conference on Middleware, held in Bangalore, India, during November 29 - December 3, 2010. The 19 papers presented have been carefully reviewed and selected from 116 submissions. The papers are organized in topical sections on cloud computing; data management; publish-subscribe and multicast systems; social and location-aware middleware; reliability and legacy; trust and security; and transactional memory.
Cloud Computing -- FLEX: A Slot Allocation Scheduling Optimizer for MapReduce Workloads -- Adapting Distributed Real-Time and Embedded Pub/Sub Middleware for Cloud Computing Environments -- BrownMap: Enforcing Power Budget in Shared Data Centers -- Data Management -- A Dynamic Data Middleware Cache for Rapidly-Growing Scientific Repositories -- Anonygator: Privacy and Integrity Preserving Data Aggregation -- Middleware for a Re-configurable Distributed Archival Store Based on Secret Sharing -- Publish-Subscribe and Multicast Systems -- Parametric Subscriptions for Content-Based Publish/Subscribe Networks -- Kevlar: A Flexible Infrastructure for Wide-Area Collaborative Applications -- FaReCast: Fast, Reliable Application Layer Multicast for Flash Dissemination -- Social and Location-Aware Middleware -- The Gossple Anonymous Social Network -- Prometheus: User-Controlled P2P Social Data Management for Socially-Aware Applications -- PerPos: A Translucent Positioning Middleware Supporting Adaptation of Internal Positioning Processes -- Reliability and Legacy -- dFault: Fault Localization in Large-Scale Peer-to-Peer Systems -- Bridging the Gap between Legacy Services and Web Services -- Trust and Security -- Enforcing End-to-End Application Security in the Cloud -- LiFTinG: Lightweight Freerider-Tracking in Gossip -- Distributed Middleware Enforcement of Event Flow Security Policy -- Transactional Memory -- Automatically Generating Symbolic Prefetches for Distributed Transactional Memories -- Asynchronous Lease-Based Replication of Software Transactional Memory.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Information Storage and Retrieval; Management of Computing and Information Systems; Computers and Society